Διερεύνηση των παραγόντων που σχετίζονται με την εμβολιαστική κάλυψη των επαγγελματιών φροντίδας υγείας κατα του ιού της γρίππης - Μαλακτού, Αγγέλα (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Introduction: Despite the recommendations of various health organizations and the campaigns conducted for vaccination against influenza to health professionals, immunization rates remain low. Knowledge attitudes and behaviours of health professionals seem to play an important role in the decision to vaccinate. Purpose: The purpose of this review is to investigate the factors associated with low rates of vaccination against influenza to health professionals and the recording of response strategies. Material and method: The method used was the search of the Greek and international literature in the database (Medline, Pubmed, Chigago Journal, Oxford journal, Google scholar) with Keywords: influenza vaccination, health care workers, attitude towards influenza vaccination among health care workers. Results: Through a literature search found that the acceptance of influenza vaccine in health professionals associated with various factors such as knowledge about vaccination safety and efficacy of the vaccine, easy access to clinics, their beliefs about health, the need for the safety of themselves, their patients and their family and others. Conclusions: need of a collective effort by all health service providers to promote vaccination to health professionals with various strategies such as providing knowledge through education and easy access and strategies that emphasize the benefits of the vaccine.
Keywords: Influenza--Vaccination; Medical personell